Public Tolerance and Private Convictions: Indonesian University Students’ Perspectives on the Childfree Lifestyle - Siti Jaro'ah; Khotamanisah; Erlina Anggraini; Siti Ina Savira (Psympathic : Jurnal Ilmiah Psikologi, 2026)
The increasing visibility of the childfree lifestyle is generating public discussion in Indonesia, particularly in relation to personal autonomy, readiness for parenthood, and religious-cultural expectations. Therefore, this study aimed to explore university students’ perspectives on the childfree phenomenon and the reasons underlying their supportive or opposing stand. The method used was a descriptive qualitative design, comprising 82 students enrolled in Gender Psychology courses at a university in Surabaya, Indonesia. Participants consisted of 67 females and 15 males aged 18-22 years, selected through purposive sampling. Data were collected using an online open-ended questionnaire and analyzed by iterative thematic analysis. The results showed that 54 and 46% of participants disagreed and agreed with the childfree choice, respectively. Supportive responses were generally framed from a public or third-person perspective, emphasizing individual autonomy, readiness, past experiences, environmental concerns, and medical factors. In contrast, opposing responses were more often expressed through personal and normative perspectives. This emphasized religious beliefs, children as successors and sources of happiness, personal desire for parenthood, and expectations of care in old age. In conclusion, the results suggest that students’ views on the childfree lifestyle are shaped by the interaction between personal evaluations, perceived readiness, and religious-cultural norms.